A pesca do Mapará (Hypophthalmus edentatus) principal atividade pesqueira da comunidade do Rio Baixo Anapu, interior do município de Igarapé-Miri - MACIEL, Maria Beatriz Portilho (2021)
This action plan is a construction of interscientific dialogues between the community and the University, created from the collective demands of the community of the Lower Anapu River, in the interior of the municipality of Igarapé-Miri. The main objective is to reformulate the Mapará fishing agreements with fishermen from the lower Anapu, with a view to alleviating conflicts and promoting collective use, sustainable practice and the conservation of fishery resources. The construction of this action plan was based on research carried out during the Times Communities (TC), discussions with colleagues and professors during the Times Universities (TU), dialogues during the meeting with community members, participant observations and bibliographic surveys. According to research carried out in my community of belonging, artisanal fishing is the most important source of food and income for families. Since the decline of plantations in the Lower Tocantins region in 1987, the commercial farmer who used fishing as a subsistence activity has become a commercial fisherman and a subsistence farmer. However, in the 1980s, artisanal fishing suffers a serious crisis after the construction of the Tucuruí Hydroelectric Power Plant (UHE) on the banks of the Tocantins River, causing a decrease in fish production, causing disputes/conflicts between riverside dwellers and fishermen. need for the creation of so-called fisheries agreements, a set of rules established by the community. In this sense, it is proposed with this action plan to define the use and access of the common resources of the Mapará fisheries in a collective and sustainable manner, as an important instrument of Ethnodevelopment, reinforcing the importance of cultural, food, income generation and, above all, autonomy over its territories.